2022
DOI: 10.3390/cells11071233
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Complex Muscle Cell In Vitro Models to Study Pathomechanisms and Drug Development of Neuromuscular Disease

Abstract: Many neuromuscular disease entities possess a significant disease burden and therapeutic options remain limited. Innovative human preclinical models may help to uncover relevant disease mechanisms and enhance the translation of therapeutic findings to strengthen neuromuscular disease precision medicine. By concentrating on idiopathic inflammatory muscle disorders, we summarize the recent evolution of the novel in vitro models to study disease mechanisms and therapeutic strategies. A particular focus is laid on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 240 publications
(272 reference statements)
0
9
0
Order By: Relevance
“…100 These techniques are of increasing interest when combined with tissue-engineered three-dimensional cultures and organoids that can more realistically represent the in vivo environment of skeletal muscle, particularly in the context of mechanical loading, electrical stimulation, and co-cultures with other cell types. [101][102][103] Critical challenges for the advancement of these complex skeletal muscle cultures include the extent of tissue maturation, consideration of myofibre-type composition, and incorporation of other organ systems. 104 Key questions for tissue culture models are how representative are they of normal human muscles and disease pathologies in vivo and how translatable are their findings to different muscles in the clinic?…”
Section: Myhc Affected a Myofibre-type Differences Slow (Type 1) Vers...mentioning
confidence: 99%
See 1 more Smart Citation
“…100 These techniques are of increasing interest when combined with tissue-engineered three-dimensional cultures and organoids that can more realistically represent the in vivo environment of skeletal muscle, particularly in the context of mechanical loading, electrical stimulation, and co-cultures with other cell types. [101][102][103] Critical challenges for the advancement of these complex skeletal muscle cultures include the extent of tissue maturation, consideration of myofibre-type composition, and incorporation of other organ systems. 104 Key questions for tissue culture models are how representative are they of normal human muscles and disease pathologies in vivo and how translatable are their findings to different muscles in the clinic?…”
Section: Myhc Affected a Myofibre-type Differences Slow (Type 1) Vers...mentioning
confidence: 99%
“…Advances in human induced pluripotent stem cell technology have enabled the generation of human skeletal muscle precursor cells (plus many other cell types) and the study of myotubes for a wide range of neuromuscular disorders 100 . These techniques are of increasing interest when combined with tissue‐engineered three‐dimensional cultures and organoids that can more realistically represent the in vivo environment of skeletal muscle, particularly in the context of mechanical loading, electrical stimulation, and co‐cultures with other cell types 101‐103 . Critical challenges for the advancement of these complex skeletal muscle cultures include the extent of tissue maturation, consideration of myofibre‐type composition, and incorporation of other organ systems 104 .…”
Section: Characterising Myofibre Typesmentioning
confidence: 99%
“…There are currently very few treatment options available for neuromuscular disorders, with some exceptions including enzyme therapy for Pompe disease and gene therapy, antisense oligonucleotides, and splice modulators for spinal muscular atrophy [ 2 4 ]. One reason for the limited number of available treatments is the lack of suitable humanized disease models that are able to mimic disease pathology and that allow the functional evaluation of novel therapeutic interventions [ 5 , 6 ]. Transgenic mouse models have been generated for many muscular dystrophies, but these often have mild phenotypes and may not (fully) represent disease mechanisms that operate in human patients due to species-specific differences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was reported that a number of muscle lineage cell lines were established in mammals. For example, the rat L6 and the mouse C2C12 myoblast cell lines were established in 1968 and 1977 [8,9], respectively, and they have been used as important experimental models to identify pathogenic and pathophysiological mechanisms in various neuromuscular diseases, as well as in therapeutic drug discovery approaches [10,11]. In pigs, the establishment of a porcine myoblast cell line with a proven differentiation capacity to myotubes was reported [12], along with the isolation of pure muscle satellite cells and their characterization [13].…”
Section: Introductionmentioning
confidence: 99%